'Cin ciun cian' (ching chong): Yellowness and neo-orientalism in Italy at the time of COVID-19. (May 2021) - Miyake, Toshio
The COVID-19 pandemic has put in the foreground the dramatic actuality of global and local inequalities, undermining neo-liberal, communitarian, democratic or cosmopolitan projects of collective identity. In the light of intersecting inequalities such as class, race/ethnicity and gender, an explosion of Sinophobia, social stigma and physical attacks targeting people of East Asian and Southeast Asian appearance or heritage has been widely reported in Euro-American media. This article will focus on the case of Italy during the initial stage of the pandemic in early 2020. Italy has not only been the first European country to be exposed to the pandemic and to undergo national lockdown but also a country where the wave of racist assaults started in late January 2020, even before the first clusters have been detected. The critical investigation of Italian media discourses will highlight how deep-rooted, colonialist and ambivalent assumptions about the 'Oriental', 'Asian', 'Chinese' and 'yellow' other may have been crucial to the reproduction of racism against specific people, cultures and civilizations, regardless of nationality, class and gender. It will refer in particular to the concept of 'yellowness', resulting from a process of bio-cultural racialization within the hegemonic frame of 'Western', 'White' or 'Italian' identity. Furthermore, it will indicate how this process of racialized othering has emerged, but has also been contested, within the specific context of citizenship, Asian immigrants and governmental actions in contemporary Italy. The overall aim is not so much to denounce higher levels of racism in Italy compared to other Euro-American countries; rather, this article refers to the Italian case to stress how both global and local trajectories do mutually overlap to shape, and eventually to transform, a national context, offering further insights on the glo-calization of the civilizational 'West'/'East' divide in the 21st century.